Development of FEA Bioelectromagnetic Model for Male’s Electromagnetic Radiation Protective Underwear (Journal of Fiber Bioengineering and Informatics, 2018)
Electromagnetic radiation is the leading cause of diseases in some special environments. With thedevelopment of functional clothing design, simulation technology have been increasingly emphasized.Understanding the electromagnetic radiation protective mechanism through a FEA Bionelectromagneticmodel is of great significance for male’s reproductive system protection. This 3D FEA Bionelectromagneticmodel includes muscle model, pelvic model, thigh bone model, bladder model, prostate model, and testismodel. The influence of silver layer and bronze layer on electromagnetic field shielding within a dressedmanikin exposed to 915 MHz were investigated. Simulated results indicated that testis were protectedmostly by electromagnetic radiation protective underwear and other tissues have received various degreesof damage. Increasing the fabric thickness was an effective method to reduce the electromagneticradiation energy. Therefore, it is important to develop a bioelectromagnetic model to research theshielding effectiveness of the product. Taking the value of electric field strength, magnetic strength andSAR to evaluate influence from radiation source. The bioelectromagnetic model could help designers toforecast the performance of electromagnetic radiation protective underwear, and the results provide thebasis for optimum design.
Keywords: Electromagnetic Radiation Protective Underwear; Bioelectromagnetic Model; Shielding Effectiveness